Contribution to the determination of the place of death by drowning – A study of diatoms' biodiversity in Douro river estuary. (July 2016) - Coelho, Sara; Ramos, Patrícia; Ribeiro, Cláudia; Marques, Joana; Santos, Agostinho
Abstract: The role of the investigation of diatoms' presence in organs and body fluids of an individual found dead in a liquid medium and the relevant contribution to the forensic diagnosis of drowning remain controversial. Furthermore, the absence of an exact and well-defined method for diatoms' analysis makes its study a challenging task. Considering this medico-legal problem and the absence of forensic studies on this subject in Portugal, this work aimed to determine the drowning place of dead individuals based on the analysis of diatom species found in different tissues (lung, liver, kidney, bone marrow) and stomach content. Diatom species found in biological samples were compared with those present in the liquid medium where the corpses were found. A total of 37 cases of death by drowning in Oporto metropolitan area were studied. A seasonal database of the diatom species found in Douro river estuary was built based on water samples collected at nine selected places. Diatoms' extractions were performed by a chemical method using 37% (w/w) hydrochloridric acid for the biological samples and 96% (w/w) sulfuric acid for water samples. Diatoms were found in 63% of total cases but only in lung and gastric content samples. The absence of diatoms in other organs is probably related with a quick death, which may have stopped blood circulation almost immediately, preventing diatom contamination of the other organs. A strong relationship between the diatom species found in the biological samples and those found in water samples of the respective drowning place was observed. Due to the high anthropogenic influence on the Douro estuary no significant differences were observed between the five sampling places, making it extremely difficult to determine the exact estuary location of the drowning. The importance of the creation of a diatom database of the potential drowning places (e.g., rivers, seas, lakes) becomes clear in this study. It also shows that, in cases of drowning, the collection of a water sample from the drowning place is crucial. This is the only way to allow a rigorous comparison of the diatom species in water and biological samples. Highlights: This work aimed to determine the drowning place of dead individuals found in a liquid medium. Diatoms were analyzed in water samples of 9 different locations along Douro river estuary. Significant differences were observed between in fresh water and salt water. A total of 37 cases of death by drowning in Oporto metropolitan area were studied.